THE INFLUENCE OF CHATBOT QUALITY ON SATISFACTION USE CHATBOT: THE ROLES OF EASE AND USEFULNESS - Catherine Christiana Tjandra; Haris Maupa; Cokki Cokki (Graduate Program of Universitas Tarumanagara, 2026)
Chatbots are becoming more popular as automated customer care solutions on e-commerce platforms due to the fast development of digital technology. The purpose of this research is to examine the relationship between chatbot quality and user happiness via the mediation of perceived utility and simplicity of use. Shopee customers in Indonesia who have engaged with the chatbot function on the site were surveyed online using a quantitative technique. Instrument validity, reliability, and the connections among the constructs were evaluated using data processed using Partial Least Squares-Structural Equation Modeling. According to the results, the perceived utility and ease of use of a chatbot are both much improved by its quality. A user's level of happiness is strongly related to their perception of the product's utility, which is in turn influenced by their impression of how easy it is to use. Exogenous factors adequately explain endogenous constructs, according to the moderate coefficient of determination. In sum, the findings demonstrate how crucial chatbot quality is for influencing users' opinions and enhancing their happiness. From a theoretical standpoint, this study further supports the relevance of the Technology Acceptance Model when discussing chatbot services for online shopping. The study provides practical insights for e-commerce operators, especially Shopee, on how to improve the quality of chatbots so that they are more interactive, easier to use, and provide users with tangible benefits. This will encourage users to continue using the bots and help develop more effective digital service strategies in the future.